Mesenchymal stem cells secrete immunologically active exosomes - Zhang, Bin; Yin, Yijun; Lai, Ruenn Chai; Tan, Soon Sim; Choo, Andre Boon Hwa; Lim, Sai Kiang (Stem cells and development, 2014)
Mesenchymal stem cells (MSCs) have been shown to secrete exosomes that are cardioprotective. Here, we demonstrated that MSC exosome, a secreted membrane vesicle, is immunologically active. MSC exosomes induced polymyxin-resistant, MYD88-dependent secreted embryonic alkaline phosphatase (SEAP) expression in a THP1-Xblue, a THP-1 reporter cell line with an NFκB-SEAP reporter gene. In contrast to lipopolysaccharide, they induced high levels of anti-inflammatory IL10 and TGFβ1 transcript at 3 and 72 h, and much attenuated levels of pro-inflammatory IL1B, IL6, TNFA and IL12P40 transcript at 3-h. The 3-h but not 72-h induction of cytokine transcript was abrogated by MyD88 deficiency. Primary human and mouse monocytes exhibited a similar exosome-induced cytokine transcript profile. Exosome-treated THP-1 but not MyD88-deficient THP-1 cells polarized activated CD4(+) T cells to CD4(+)CD25(+)FoxP3(+) regulatory T cells (Tregs) at a ratio of one exosome-treated THP-1 cell to 1,000 CD4(+) T cells. Infusion of MSC exosomes enhanced the survival of allogenic skin graft in mice and increased Tregs.